Educational media in Portugal: the next decade (2011-2020) - Teixeira, António (2022)
A discussion on the future developments on educational media in the context of higher education in Portugal will be the focus of this panel. This panel will represent different lines of research and development as well as a variety of experiences on implementing innovation in higher education. The panelists will share their expectations and visions for a next decade of development and innovation in the area of educational media in Portugal.